From egg to sea turtle - Owings, Lisa (Minneapolis : Lerner Publications, 2017)
"How does a sea turtle grow from a tiny hatchling into a huge animal? Dual-level text and color photos aid beginning and advanced readers as they learn about each step in a sea turtle's life."--
Includes bibliographical references and index.
Ages 5-9.
K to grade 3.
Keywords: Sea turtles -- Juvenile literature; Sea turtles -- Development -- Juvenile literature; Literature